2013
DOI: 10.1002/ejoc.201300692
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Enantioselective Synthesis of β‐Amino Alcohols from 1,2‐Diols by “Borrowing Hydrogen”

Abstract: Enantioselective synthesis of β‐amino alcohols from 1,2‐diols by the use of [RuCl2(p‐cymene)]2/(S,R)‐JOSIPHOS catalysis was developed. Several 1,2‐diols were treated with secondary amines to afford the corresponding optically active β‐amino alcohols in up to 99 % yield with 77 % ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…99 The hydrogen borrowing mechanism removes chirality in a secondary alcohol substrate during the oxidation step, resulting a racemic product after reduction, however, asymmetric variants of the reaction are emerging with the use of a ruthenium catalyst and a chiral Josiphos ligand in the enantioselective preparation of β-aminoalcohols from racemic diols, via an asymmetric hydrogenation of an intermediate ketone. 100 The use of Ellman's chiral sulfinamide auxiliary enabled ruthenium catalysed preparation of enantiomerically enhanced amines from racemic secondary alcohols 101 and use of chiral phosphoric acids as an additive in combination with an iridium catalyst enabled preparation of chiral amines. 102 Given the amount of progress made in all alcohol activation approaches it is surprising to find few published reports of scale-up of direct substitution approaches towards the preparation of pharmaceutically relevant substrates.…”
Section: Direct Substitution Of Alcoholsmentioning
confidence: 99%
“…99 The hydrogen borrowing mechanism removes chirality in a secondary alcohol substrate during the oxidation step, resulting a racemic product after reduction, however, asymmetric variants of the reaction are emerging with the use of a ruthenium catalyst and a chiral Josiphos ligand in the enantioselective preparation of β-aminoalcohols from racemic diols, via an asymmetric hydrogenation of an intermediate ketone. 100 The use of Ellman's chiral sulfinamide auxiliary enabled ruthenium catalysed preparation of enantiomerically enhanced amines from racemic secondary alcohols 101 and use of chiral phosphoric acids as an additive in combination with an iridium catalyst enabled preparation of chiral amines. 102 Given the amount of progress made in all alcohol activation approaches it is surprising to find few published reports of scale-up of direct substitution approaches towards the preparation of pharmaceutically relevant substrates.…”
Section: Direct Substitution Of Alcoholsmentioning
confidence: 99%
“…Williams and co‐workers also used a chiral amine substrate in a Ru‐catalyzed amination of alcohols with retention of chirality in the product, albeit with no new chiral center generated . In 2013, Oe and co‐workers reported the first asymmetric alkylation of achiral amines with racemic alcohols with a chiral Ru catalyst, affording moderate ee values (<70 %) . A major breakthrough was made by Zhao and co‐workers in 2014, who showed that chiral amines of up to greater than 99 % ee can be formed by reacting achiral amines with racemic alcohols using a chiral Ir catalyst in conjunction with a chiral phosphoric acid (Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…7 Similarly, Oe reported the regioselective amination of 1-phenyl-1,2-ethanediol with secondary amines (5 mol% Ru and ( S,R )-Josiphos). 8 …”
Section: Resultsmentioning
confidence: 99%